2015
DOI: 10.1080/00223131.2015.1087353
|View full text |Cite
|
Sign up to set email alerts
|

CHF enhancement by honeycomb porous plate in saturated pool boiling of nanofluid

Abstract: One strategy for severe accidents is in-vessel retention (IVR) of corium debris. In order to enhance the capability of IVR in the case of a severe accident involving a light-water reactor, methods to increase the critical heat flux (CHF) should be considered. Approaches for increasing the IVR capability must be simple and installable at low cost. Moreover, cooling techniques for IVR should be applicable to a large heated surface. Therefore, as a suitable cooling technology for required conditions, we proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 46 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…In recent years, as described by Okawa et al (2014), research on the improvement of 𝑞𝑞 CHF has been conducted using nanofluids Cheng et al, 2008;Kim, 2011;Kwark et al, 2010;Mori et al, 2014Mori et al, , 2015aMori et al, , 2016Mt Aznam et al, 2015Okawa et al, 2012;You et al, 2003). The improvement rate is in a wide range of 1.1 to 3 times compared to the bare surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as described by Okawa et al (2014), research on the improvement of 𝑞𝑞 CHF has been conducted using nanofluids Cheng et al, 2008;Kim, 2011;Kwark et al, 2010;Mori et al, 2014Mori et al, , 2015aMori et al, , 2016Mt Aznam et al, 2015Okawa et al, 2012;You et al, 2003). The improvement rate is in a wide range of 1.1 to 3 times compared to the bare surface.…”
Section: Introductionmentioning
confidence: 99%
“…Mori and Okuyama (2009) proposed a surface modification by attaching a honeycomb porous plate (HPP) to a heated surface. For upward-facing φ 30 mm and φ 50 mm heater surfaces with an HPP attached, saturated pool boiling 𝑞𝑞 CHF under atmospheric pressure with water was reported to be enhanced up to 2.5 times as compared to a bare surface (Mori et al, 2016;. The HPP provides two vital parts, which are the porous part and vapor escape channels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lotfi and Shafii [209] reported CHF reduction for 0.5-4 wt% Ag and 0.125-1.0 wt% TiO 2 nanofluids as the nanoparticle concentration decreases. The boiling properties of a honeycomb porous plate, which covers a 30-mm diameter heating surface that was placed in water-based TiO 2 nanofluids was studied by Mori et al [210,211]. They achieved considerable CHF amelioration equal to 320 W/cm 2 by increasing the nanoparticle concentration to 0.1 vol.%.…”
Section: Nanoparticle Concentrationmentioning
confidence: 99%
“…Various methods have been proposed for enhancing IVR performance and reliability, including using nanofluids [2][3][4][5] or surfactant solutions [6][7][8] instead of water and modifying the RPV outer wall [9][10][11][12][13][14]. Mori et al [15] proposed a combination of two approaches, the adoption of TiO 2 nanofluid as coolant and the attachment of a honeycomb porous plate (HPP) to the RPV outer wall to improve the critical heat flux (CHF). They found that the CHF increased when using the nanofluid concentrations tested (0 vol%, 0.001 vol%, and 0.1 vol%), with a CHF of 3.2 MW/m 2 for 0.1 vol% nanofluid with an HPP attached to the surface.…”
Section: Introductionmentioning
confidence: 99%